ETIKA PENYELENGGARA TENAGA PEREKAM MEDIS DALAM UPAYA PENCEGAHAN KEBOCORAN DATA DAN INFORMASI MEDIS PASIEN DI RSUD DR. HASRI AINUN HABIBIE - Dangkua, Fahria; Ahmad, Riska; Katili, Rismunandar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The confidentiality of patients’ medical data and information is a crucial aspect of healthcare services, particularly in the era of digitalized medical records that requires stronger information security. The use of hospital information systems facilitates healthcare services; however, it also increases the risk of data breaches if not properly managed. Medical record officers play a vital role in maintaining data security in accordance with applicable regulations. Based on this urgency, this study was conducted to identify potential risks of data breaches and preventive efforts at RSUD Dr. Hasri Ainun Habibie. This study employed a qualitative descriptive method with a normative–empirical approach. Data were collected through in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results indicate that the hospital has implemented several security measures, including the use of individual passwords, two-factor authentication, access restrictions, and data backup within the hospital information system. Nevertheless, risks still arise from human resource factors, such as limited understanding of data security, the potential for human error, and network constraints. In addition, specific training on data confidentiality and professional ethics has not yet been conducted. In conclusion, the role of medical record officers is essential in preventing data breaches. Strengthening competencies, increasing training programs, and reinforcing information security policies are necessary to ensure optimal protection of patients’ data.